Women Leaders Transcending the Demands of Covid-19: A Positive Psychology 2.0 Perspective - Mayer, Claude-Hélène; May, Michelle S. (Frontiers in Psychology, 2021)
This is a study of selected speeches of three global women leaders during the time of the Covid-19 pandemic, from positive psychology perspectives. It focuses on speeches about managing the pandemic by global women leaders such as Angela Merkel (Germany), Jacinda Ardern (New Zealand), and Tsai Ing-wen (Taiwan). This study explores the question of what global women leaders’ leadership actions and responses are, and how they addressed their nations with regard to the four pillars of PP2.0 and the PURE model during Covid-19. The authors use a post-modernist qualitative research design. The study is in the hermeneutical-phenomenological research paradigm, with leadership theories and PP2.0 used as a lens to explore and understand women leaders’ strengths with regard to the Covid-19 pandemic. The authors analyse thematically the selected speeches made by the three women leaders at the onset of the pandemic in Germany, New Zealand and Taiwan. The study contributes to the understanding of global women’s leadership during Covid-19. Conclusions are drawn and recommendations are made .